The effect of increased nitrogen load on phytoplankton in a phosphorus‐limited lake. (November 2016) - Poxleitner, Monika; Trommer, Gabriele; Lorenz, Patrick; Stibor, Herwig
Summary: Widespread use of artificial fertilisers and the burning of fossil fuels and/or biomass release a large amount of reactive nitrogen into the atmosphere. So far, the effects of increasing nitrogen deposition from the atmosphere have mainly been studied in nitrogen‐limited limnic and marine systems. Interestingly, in phosphorus‐limited lakes, additional nitrogen input might not affect phytoplankton biomass, but rather increase mainly the degree of phosphorus limitation. The resulting effects on plankton communities are difficult to predict and quantify. To estimate the effects of increasing nitrogen load on a spring phytoplankton community in a primarily phosphorus‐limited system, a mesocosm experiment was performed in an oligotrophic lake, in which a gradient of six increasing nitrogen enrichment levels was applied. During the initial phytoplankton growth phase (spring bloom), molar, seston nitrogen:phosphorus ratios increased from 43 to 72 and carbon:phosphorus ratios from 328 to 542 with increasing nitrogen enrichment, indicating increased phosphorus limitation. Three commonly used phytoplankton biomass proxies (phytoplankton biovolume, chlorophyll a and particulate organic carbon) showed only minor responses to nitrogen enrichment. Different groups and species of phytoplankton varied in their responses to the nitrogen enrichment in both the growth phase (spring bloom) and the descending phase (clear water phase). Overall, we detected an effect of nitrogen enrichment on phytoplankton stoichiometry and community composition. The observed changes in the phytoplankton community combined with changes in abundances of heterotrophic nanoflagellates and ciliates indicate bottom‐up driven alterations of the basal food web due to increased nitrogen loads.